CeO2 decorated bimetallic phosphide nanowire arrays for enhanced oxygen evolution reaction electrocatalysis via interface engineering. Issue 7 (1st February 2022) - Cong, Yikang; Chen, Xingnan; Mei, Yan; Ye, Jun; Li, Ting-Ting
Abstract : A novel heterostructure comprising of Co0.4 Ni1.6 P nanowire arrays decorated with CeO2 nanoparticles grown on porous Ni foam is easily fabricated and shows remarkable OER performance. Abstract : To realize electrocatalytic water splitting for hydrogen production, the development of efficient and durable anode materials containing earth-abundant elements is of great significance. In this work, we demonstrate a novel heterostructure with easily depositing CeO2 nanoparticles on the surface of the metal–organic framework (MOF)-derived Co0.4 Ni1.6 P nanowire arrays. Such an interface engineering strategy triggers the formation of abundant oxygen vacancies and provides more electrocatalytically active sites. Besides, the synergistic effect in this composite can regulate the electronic structure, and lead to an enhanced charge-transfer ability. Benefiting from the above superiorities, this heterostructure exhibits remarkable electrocatalytic performance towards the oxygen evolution reaction (OER) in 1 M KOH electrolyte, requiring overpotentials ( η ) of 268 and 343 mV to yield current densities of 10 and 100 mA cm −2, respectively, accompanied by a low Tafel slope of 79.3 mV dec −1 . Furthermore, the electrocatalytic performance of this heterostructure for the OER in simulated alkaline seawater (1 M KOH + 0.5 M NaCl) was also studied, and it achieved low η values of 345 and 394 mV to drive 100 and 200 mA cm −2, respectively. This work presents a simple approach to fabricate heterostructural electrocatalysts with CeO2 nanoparticles for high-performance water/seawater electrolysis.